Memória, ansiedade e função motora na prole de ratas com hipotireoidismo gestacional - Menezes, Edênia da Cunha (2014)
Maternal thyroid hormones (THs) are crucial for fetal development, especially to the central nervous system. Changes in maternal THs levels during pregnancy can result in many organic disorders over the life of the offspring. We aimed to investigate the impact of the lack of maternal THs during the pregnancy in the memory, anxiety and motor function in the offspring. Hypothyroidism was induced by ad libitum administration of 0.02% methimazole (MMI) in drinking water, from 9th day of pregnancy until delivery day. At 75 and 120 postnatal day (75 and 120 PND), the offspring (males) from MMI-treated dams (OMTD) and water-treated dams (OWTD) were subjected to different tests: i. spontaneous alternation (SAT), object recognition (OR), hole board (HB), free exploration paradigm (FEP), catalepsy (CT) and open field (OF). To evaluate short term memory we used SAT and OR. State and trait anxiety were evaluated by HB and FEP, respectively. The motor function was accessed by CT and OF. Statiscal test for homoscedasticity (Levene) and normality (Shapiro-Wilks) were applied. Data with normal distribution and homoscedastic were analyzed by unpaired one sample t-test. Non-normal and non-homoscedastic data were analyzed by non-parametric Mann Whitney test. When required, two-way ANOVA followed by Bonferroni post-hoc was used. Both, SAT and OR showed that OMTD had lower short term memory. In SAT, OMTD presented lower percentage of complete alternations compared to OWTD, at 75 and 120 PND, (p<0.001; p<0.01, respectively). At 75 and 120 PND, OMTD were not able to discriminate new and old objects (p=0.26; p=0.70) in OR test. OMTD spent less time exploring both objects, but only at 120 PND, regardless of the session (p<0.01). A decreased anxiety state was evidenced in OMTD by the increased number of head-dip on the HB test, both at 75 (p<0.05) and 120 PND (p<0.05), as well as by the increase in time spent in head-dip, only at 120 PND (p<0.01). Moreover, no changes were observed on the anxiety profile of OMTD subjected to FEP in both studied ages. We also observed an increase on the cataleptic behavior on OMTD, by the greater time spent in the apparatus bar, both at 75 (p<0.05) and 120 PND (p<0.01). The ambulation on OF didn´t differed between the groups. Thus, this study demonstrated, for the first time, that the lack of maternal THs during the pregnancy reduces the short-term memory, motor function and state anxiety of offspring of rats. The increased catatonic behavior in OMTD suggests loss of motivation and/or anhedonia.